2005
DOI: 10.1002/hbm.20140
|View full text |Cite
|
Sign up to set email alerts
|

Stuttered and fluent speech production: An ALE meta‐analysis of functional neuroimaging studies

Abstract: Abstract:This study reports an activation likelihood estimation (ALE) meta-analysis of imaging studies of chronic developmental stuttering in adults. Two parallel meta-analyses were carried out: (1) stuttered production in the stutterers; (2) fluent production in the control subjects. The control subjects' data replicated previous analyses of single-word reading, identifying activation in primary motor cortex, premotor cortex, supplementary motor area, Rolandic operculum, lateral cerebellum, and auditory areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

41
353
6
8

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 362 publications
(408 citation statements)
references
References 77 publications
(109 reference statements)
41
353
6
8
Order By: Relevance
“…First, previous research identified the overactivation of the right cerebellum as a neural signature of stuttering (Brown et al, 2005) and as specific to stuttered speech (Braun et al, 1997;Fox et al, 1996). Although the participants in this study produced fluent speech during the experiment, we also found overactivation in the right cerebllum.…”
Section: The Neural Substrates For Atypical Execution Process In Stutmentioning
confidence: 38%
See 2 more Smart Citations
“…First, previous research identified the overactivation of the right cerebellum as a neural signature of stuttering (Brown et al, 2005) and as specific to stuttered speech (Braun et al, 1997;Fox et al, 1996). Although the participants in this study produced fluent speech during the experiment, we also found overactivation in the right cerebllum.…”
Section: The Neural Substrates For Atypical Execution Process In Stutmentioning
confidence: 38%
“…In a previous meta-analysis, the right IFG and anterior insula were, as a whole, considered to be one of the neural signatures of stuttering (Brown et al, 2005). Our results, however, suggest that their roles in stuttering may be different.…”
Section: The Neural Substrates For Atypical Execution Process In Stutmentioning
confidence: 44%
See 1 more Smart Citation
“…It is well established that speech production involves the sensorimotor cortex, SMA, inferior frontal gyrus/ventral premotor cortex (PMv), superior temporal gyrus (STG)/Heschl's gyrus, and cerebellum (Brown, Ingham, Ingham, Laird, & Fox, 2005; Brown et al., 2009; Manes et al., 2014; Tourville & Guenther, 2011) These regions of the cortex are reliably active during speech and voice production tasks (Brown et al., 2005; Manes et al., 2014; Spaniol et al., 2009). Studies of whole‐brain resting‐state connectivity in PD have documented that the basal ganglia have abnormal connectivity to the cerebellum (Hacker, Perlmutter, Criswell, Ances, & Snyder, 2012) and motor cortices, including sensorimotor cortex (Baudrexel et al., 2011; Hacker et al., 2012; Kurani et al., 2015; Kwak et al., 2010), premotor cortex (Baudrexel et al., 2011), and SMA (Baudrexel et al., 2011; Hacker et al., 2012; Kwak et al., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…New et al. (2015) found that PD subjects had reduced connectivity between right and left putamen after performing a seed to seed resting‐state connectivity analysis on thirteen regions involved in vocal motor control (Brown et al., 2005). The study further found that UPDRS Part III speech impairment scores were inversely correlated with right putamen connectivity to right cerebellum and left STG.…”
Section: Introductionmentioning
confidence: 99%